Pension benefits outside of the pension system - Ólafur Ísleifsson 1955- (2013)
Fræðigrein In this paper we review a special pension scheme established by the Government of Iceland for elderly workers that foreseeably would not enjoy any significant pension benefits from the pension system founded on the basis of the general labour agreements of 1969. This pension scheme that was run alongside the private labour market pension system and social security was conceived as a temporary measure but extended over a longer time period than originally envisaged. Based on unpublished data we seek answers to questions on the financing of the scheme and its impact in terms of the relative share of its pension payments.